2007
DOI: 10.1016/j.neuroscience.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

I.v. cocaine induces rapid, transient excitation of striatal neurons via its action on peripheral neural elements: Single-cell, iontophoretic study in awake and anesthetized rats

Abstract: Cocaine's (COC) direct interaction with the dopamine (DA) transporter is usually considered the most important action underlying the psychomotor stimulant and reinforcing effects of this drug. However, some physiological, behavioral and psycho-emotional effects of COC are very rapid and brief and they remain intact during DA receptor blockade, suggesting possible involvement of peripheral non-DA neural mechanisms.To assess this issue, single-unit recording with microiontophoresis was used to examine changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 73 publications
(91 reference statements)
4
40
0
Order By: Relevance
“…Cocaine was injected via catheter and extending tubing, in low volume and at low speed, and special care has been taken to exclude any possible sensory cues associated with drug injection. Although the complexity of VTA cell recording in the awake conditions made it difficult to evaluate the effects of saline on each cellular subgroup, we previously showed that such injections performed at the same conditions did not affect animal behavior, brain, skin, and muscle temperatures (Brown and Kiyatkin, 2006) as well as impulse activity of striatal neurons (Kiyatkin and Brown, 2007). No effects of low-volume saline injections on VTA cell activity have been also documented in our heroin self-administration studies (Kiyatkin and Rebec, 2001).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Cocaine was injected via catheter and extending tubing, in low volume and at low speed, and special care has been taken to exclude any possible sensory cues associated with drug injection. Although the complexity of VTA cell recording in the awake conditions made it difficult to evaluate the effects of saline on each cellular subgroup, we previously showed that such injections performed at the same conditions did not affect animal behavior, brain, skin, and muscle temperatures (Brown and Kiyatkin, 2006) as well as impulse activity of striatal neurons (Kiyatkin and Brown, 2007). No effects of low-volume saline injections on VTA cell activity have been also documented in our heroin self-administration studies (Kiyatkin and Rebec, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…Most striatal neurons show rapid, transient excitations of a similar amplitude and time course following tail-press, tail-pinch, iv cocaine and cocaine methiodide in awake conditions, but these effects are dramatically attenuated or fully blocked during urethane anesthesia (Kiyatkin and Brown, 2007). While this study was limited to the awake conditions and we were unable to test the effects of peripherally acting cocaine methiodide (experiments in progress), it is reasonable to assume that general anesthesia, in addition to modulating spontaneous impulse activity, should inhibit the sensory responses of VTA neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations